Diurnal and circadian expression profiles of glycerolipid biosynthetic genes in Arabidopsis - Nakamura, Yuki (Landes Bioscience, 2014)
Glycerolipid composition in plant membranes oscillates in response to diurnal change. However, its functional significance remained unclear. A recent discovery that Arabidopsis florigen FT binds diurnally oscillating phosphatidylcholine molecules to promote flowering suggests that diurnal oscillation of glycerolipid composition is an important input in flowering time control. Taking advantage of public microarray data, we globally analyzed the expression pattern of glycerolipid biosynthetic genes in Arabidopsis under long-day, short-day, and continuous light conditions. The results revealed that 12 genes associated with glycerolipid metabolism showed significant oscillatory profiles. Interestingly, expression of most of these genes followed circadian profiles, suggesting that glycerolipid biosynthesis is partially under clock regulation. The oscillating expression profile of one representative gene, PECT1, was analyzed in detail. Expression of PECT1 showed a circadian pattern highly correlated with that of the clock-regulated gene GIGANTEA. Thus, our study suggests that a considerable number of glycerolipid biosynthetic genes are under circadian control.